Development of Augmented Reality Based Interactive Learning Media on Electric Motor Installation Subjects - Muskhir, Mukhlidi; Luthfi, Afdal; Sidiq, Hazmi; Fadillah, Rahmat (Society of Visual Informatics, 2024)
Interactive learning media play an essential role in the learning process. In today's digital era, interactive learning media is one of the best choices for improving the quality of learning by making it more effective and efficient. This study aims to develop augmented reality (AR)–based interactive learning media for electric motor installation subjects. The method used in this research is the research and development (R&D) method with the 4-D development model. This research consists of several stages: defining, designing, developing, and disseminating. Based on the research results, it can be concluded that this augmented reality learning media development research has produced a valid and practical augmented reality learning medium for electric motor installation subjects. The media and material validation results consist of two media validators and two material validators. Obtained a media validation value of 0.58 and a material validation value of 0.62 using the validity interval category ≥ 0.4. Thus, the media and materials developed were declared valid. The augmented reality learning media practicality test results obtained 86.63% by using the practicality interval category > 75%–100%. Thus, AR-based learning media in electric motor installation have been considered practical. Implications for further research could include developing AR media for other subjects or applying AR technology in various learning contexts, including integrating more complex interactive features or adapting the media for broader educational needs. In addition, this research could encourage exploring AR in distance learning scenarios and increase student engagement through gamification or further simulation in skills-based learning.